Sobrevida en leucemias agudas en pacientes hospitalizados menores de 18 años - Baca Quiroz, Anghie Ximena (2019)
Objective: To determine the survival rate in acute leukemia in patients under 18 years of age diagnosed in the Belen de Trujillo Hospital during the 2008-2015 period. Materials and Methods: A retrospective, descriptive study of patients under 18 years of age who presented acute leukaemias (AML and ALL) in the period from January 2008 to December 2015 at the Belén de Trujillo hospital. Results: 213 patients with acute leukaemias in the Belén Hospital of Trujillo, 66 suitable for the study. The number of patients found with ALL was 47 and with AML, 19. The patients with ALL were 21 women and 26 men. The patients with AML were 10 women and 9 men. Using the Kaplan - Meyer Estimator, the survival time for ALL by 2018 is 80,157 months; also the survival time for AML is 54,892 months. The overall survival time this is 71,803 months. Conclusions: The survival rate of ALL in patients under 18 diagnosed in the Hospital Belén de Trujillo was 59.5%, the AML rate was 15.78%. The overall survival rate of acute leukemias was 46.9%.